Change of Water Content, Fresh Weight and Dry Weight of Complete Feed Silage Based Rice Straw and Mulberry Biomass - Syahrir, Syahriani; Rasjid, Syamsuddin; Mide, Muhammad Zain; Harfiah, . (Buletin Nutrisi dan Makanan Ternak, 2014)
Fermentation process that takes place during the making of silage material allows moisture silage will change compared to before made silage, even ensilase process can increase or decrease the nutrients contained in the complete feed. This study examines the changes in water content, fresh weight and dry weight of complete feed silage compared with the complete feed silage has not been made. It is associated with the loss of nutrients that are used in the fermentation process or otherwise there is an increased nutrients formed by the fermentation process. Treatment consisted of six different compositions complete feed silage made, namely: J1 = 50% rice straw + concentrate + 50% 0% mulberry biomass;            J2 = 50% rice straw + 40% + 10% concentrate mulberry biomass; A = 50% rice straw + 30% + 20% concentrate mulberry biomass; J4 = 50% rice straw + 20% + 30% concentrate mulberry biomass; J5 = 50% rice straw + 10% + 40% concentrate mulberry biomass and J6 = 50% rice straw + 0% + 50% concentrate mulberry biomass. The results showed that the weight of the material per unit of fresh whole experiment was not significantly different, there are significant differences in the changes in the water content, fresh weight and dry weight of the material before and after made silage.